ISLAMIC LEARNING MODEL FOR STREET CHILDREN : AN ANALYSIS OF PSYCHOLOGICAL REINFORCEMENT - Elma, Elma; Anggraeni, Femia Dwita; Rahmatullah, Azam Syukur; Nur Aziz, Akbar (Jurnal Konseling Pendidikan Islam, 2024)
This study aims to analyze the Islamic learning model for street children. Street children are children who spend their time on the streets to live, work, play, study, and so on. The reasons these children choose to live on the streets are mostly due to internal family and economic conditions. This research uses qualitative methods with a literature review study approach. A literature review is a research method in which the way to collect data is to read, understand, and review previous articles, books, and journals. The result of this study is that the Islamic learning model that is suitable to be applied to street children is a religious humanist model. Islamic religious education can be integrated with psychological methods that support the development of street children. The combination of Islamic religious values and a good psychological approach can help shape the character of these children, give them hope, and guide them toward a better life. Therefore, investment and attention to Islamic religious education for street children should be considered an important effort in creating a better generation in the future. Based on the discussion in this paper, further research is needed related to Islamic learning methods and effective psychological approaches for street children. In addition, the role of the government is needed to help overcome the problem of street children's education.